Non-aqueous electrolyte secondary battery
Patent Information
- Application Number
- JP2024224253
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-09-27
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2040-08-28
Smart Images

Figure 2025031820000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a non-aqueous electrolyte secondary battery. [Background technology]
[0002] In recent years, lithium transition metal composite oxides with a high Ni content have been attracting attention as a positive electrode active material with high energy density. For example, Patent Document 1 describes a positive electrode active material that is mainly composed of Ni and Li and has the general formula Li x Ni 1-p-q-r Co p Al q A r O 2-y (A is at least one element selected from the group consisting of Ti, V, In, Cr, Fe, Sn, Cu, Zn, Mn, Mg, Ga, Ni, Co, Zr, Bi, Ge, Nb, Ta, Be, Ca, Sr, Ba, and Sc) and a nonaqueous electrolyte secondary battery containing a composite oxide composed of single crystal primary particles having an average particle size of 2 μm to 8 μm. Patent Document 1 describes that the characteristics of the positive electrode active material include low reactivity with the electrolyte, low internal resistance when used in a battery, and high resistance to pressure during molding of the positive electrode.
[0003] Patent Document 2 discloses a positive electrode active material whose particle surface is coated with boron oxide. Patent Document 2 states that the use of this positive electrode active material suppresses side reactions between the active material and the electrolyte, and suppresses gas generation inside the battery. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2006-54159 A [Patent Document 2] JP 2010-40382 A Summary of the Invention
[0005] In non-aqueous electrolyte secondary batteries such as lithium ion batteries, particle cracking of the positive electrode active material may occur during charging and discharging, causing an increase in resistance and a decrease in battery capacity. In particular, when large particles composed of many primary particles are cracked, many primary particles are generated that are isolated from the conductive path, and the rate of increase in resistance increases. Such cycle deterioration becomes more pronounced as the battery temperature during charging and discharging increases.
[0006] In addition, by having a boron compound on the particle surface of the positive electrode active material, side reactions between the active material and the electrolyte are suppressed, and it is expected that the resistance retention rate during high-temperature cycles will be improved. However, it is expected that the boron compound will become a resistive layer and deteriorate the rate characteristics.
[0007] An object of the present disclosure is to improve the high-temperature cycle characteristics of a high-capacity nonaqueous electrolyte secondary battery that contains a lithium transition metal composite oxide with a high Ni content as a positive electrode active material, without impairing other battery characteristics.
[0008] A non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a positive electrode containing a positive electrode active material, a negative electrode, and a non-aqueous electrolyte. The positive electrode contains, as the positive electrode active material, a lithium transition metal composite oxide (A) having a volume-based median diameter (D50) of 0.6 μm to 3 μm, which is a secondary particle formed by agglomeration of primary particles having an average particle diameter of 0.5 μm or more, or which is composed of substantially single particles, and a lithium transition metal composite oxide (B) having a volume-based median diameter (D50) of 6 μm to 25 μm, which is a secondary particle formed by agglomeration of primary particles having an average particle diameter of 0.3 μm or less. The lithium transition metal composite oxide (A) is represented by the general formula Li a Ni b Co c Mn d B e O f (wherein, 0.8≦a≦1.2, b≧0.70, c≦0.10, 0.03≦d≦0.12, 0≦e≦0.05, 1≦f≦2, b+c+d+e=1). The lithium transition metal composite oxide (B) is a composite oxide represented by the general formula Li a Ni b Co c Mn d B e Of (wherein 0.8≦a≦1.2, b≧0.70, c≦0.10, 0.03≦d≦0.12, 0.001≦e≦0.05, 1≦f≦2, b+c+d+e=1), in which boron is present at least on the particle surface of the oxide, and in the lithium transition metal composite oxide (B), when particles having a particle size larger than the 70% particle size on a volume basis (D70) are defined as first particles and particles having a particle size smaller than the 30% particle size on a volume basis (D30) are defined as second particles, the molar fraction (B1) of boron relative to the total moles of metal elements excluding Li in the first particles is larger than the molar fraction (B2) of boron relative to the total moles of metal elements excluding Li in the second particles.
[0009] The nonaqueous electrolyte secondary battery according to the present disclosure has excellent high-temperature cycle characteristics, high energy density, and other favorable battery characteristics such as rate characteristics. [Brief description of the drawings]
[0010] [Figure 1] 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery according to an embodiment; [Diagram 2] FIG. 2 is a cross-sectional view of a positive electrode according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The inventors of the present invention have conducted extensive research to solve the above problems, and have succeeded in achieving both high energy density and excellent high-temperature cycle characteristics by using lithium transition metal composite oxides (A) and (B) in combination and by making the molar fraction of boron contained in the first particles having a large particle size in the composite oxide (B) higher than the molar fraction of boron contained in the second particles having a small particle size. Since the composite oxide (A) has a smooth particle surface, it is believed that the composite oxides can be efficiently packed in the composite layer while mitigating the pressure during rolling of the positive electrode composite layer and the stress caused by the volume change of the composite layer during charging and discharging. This suppresses cracking of the composite oxide particles and increases the density of the composite layer.
[0012] In addition, by incorporating a large amount of boron, which suppresses side reactions with the electrolyte, into the first particles, which are large particles that are greatly affected by particle cracking, the cracking of the first particles can be further suppressed. On the other hand, by making the amount of boron contained in the second particles, which are small particles, less than that of the first particles, good rate characteristics can be ensured. It is believed that the nonaqueous electrolyte secondary battery according to the present disclosure has achieved high energy density and excellent high-temperature cycle characteristics due to the synergistic effect of the above-mentioned mitigation effect of the composite oxide (A) and the change in the amount of boron added depending on the particle size of the composite oxide (B).
[0013] An example of an embodiment of a nonaqueous electrolyte secondary battery according to the present disclosure will be described in detail below. A cylindrical battery in which a wound electrode body 14 is housed in a cylindrical exterior can 16 with a bottom will be exemplified below, but the exterior can is not limited to a cylindrical exterior can, and may be, for example, a rectangular exterior can, or an exterior made of a laminate sheet including a metal layer and a resin layer. The electrode body may also be a laminated type electrode body in which multiple positive electrodes and multiple negative electrodes are alternately laminated with separators between them.
[0014] FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 according to an embodiment. As illustrated in FIG. 1, the nonaqueous electrolyte secondary battery 10 includes a wound electrode assembly 14, a nonaqueous electrolyte, and an exterior can 16 that accommodates the electrode assembly 14 and the electrolyte. The electrode assembly 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The exterior can 16 is a cylindrical metal container with a bottom that is open on one axial side, and the opening of the exterior can 16 is closed by a sealing body 17. In the following description, for convenience of explanation, the sealing body 17 side of the battery is referred to as the top, and the bottom side of the exterior can 16 is referred to as the bottom.
[0015] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. Examples of the non-aqueous solvent include esters, ethers, nitriles, amides, and mixtures of two or more of these. The non-aqueous solvent may contain a halogen-substituted compound in which at least a portion of the hydrogen of these solvents is replaced with a halogen atom such as fluorine. The electrolyte salt may include, for example, LiPF 6The electrolyte is not limited to a liquid electrolyte, and may be a solid electrolyte using a gel polymer or the like.
[0016] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all long strip-shaped bodies, and are alternately stacked in the radial direction of the electrode body 14 by being wound in a spiral shape. The negative electrode 12 is formed to be slightly larger than the positive electrode 11 in order to prevent lithium deposition. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in the longitudinal direction and the width direction (short direction). The two separators 13 are formed to be at least slightly larger than the positive electrode 11, and are arranged to sandwich the positive electrode 11, for example. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0017] Insulating plates 18 and 19 are disposed above and below the electrode body 14. In the example shown in Fig. 1, the positive electrode lead 20 passes through a through hole in the insulating plate 18 and extends toward the sealing body 17, and the negative electrode lead 21 passes outside the insulating plate 19 and extends toward the bottom side of the outer casing 16. The positive electrode lead 20 is connected to the lower surface of an internal terminal plate 23 of the sealing body 17 by welding or the like, and a cap 27, which is a top plate of the sealing body 17 and is electrically connected to the internal terminal plate 23, serves as a positive electrode terminal. The negative electrode lead 21 is connected to the inner bottom inner surface of the outer casing 16 by welding or the like, and the outer casing 16 serves as a negative electrode terminal.
[0018] A gasket 28 is provided between the exterior can 16 and the sealing body 17 to ensure airtightness inside the battery. The exterior can 16 has a grooved portion 22 formed therein, with part of the side surface protruding inward, to support the sealing body 17. The grooved portion 22 is preferably formed in an annular shape along the circumferential direction of the exterior can 16, and supports the sealing body 17 on its upper surface. The sealing body 17 is fixed to the top of the exterior can 16 by the grooved portion 22 and the open end of the exterior can 16 which is crimped against the sealing body 17.
[0019] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cap 27 are laminated in this order from the electrode body 14 side. Each member constituting the sealing body 17 has, for example, a disk shape or a ring shape, and each member except the insulating member 25 is electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective centers, and the insulating member 25 is interposed between their respective peripheral edges. When the internal pressure of the battery increases due to abnormal heat generation, the lower valve body 24 deforms and breaks so as to push the upper valve body 26 toward the cap 27, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure further increases, the upper valve body 26 breaks, and gas is discharged from the opening of the cap 27.
[0020] The positive electrode 11, the negative electrode 12, and the separator 13 that constitute the electrode assembly 14, and in particular the positive electrode active material that constitutes the positive electrode 11, will be described in detail below.
[0021] [Positive electrode] FIG. 2 is a diagram showing a part of a cross section of the positive electrode 11. As illustrated in FIG. 2, the positive electrode 11 has a positive electrode core 30 and a positive electrode composite layer 31 provided on the surface of the positive electrode core 30. For the positive electrode core 30, a foil of a metal such as aluminum that is stable in the potential range of the positive electrode 11, a film in which the metal is arranged on the surface layer, or the like can be used. The positive electrode composite layer 31 contains a positive electrode active material, a binder, and a conductive material, and is preferably provided on both sides of the positive electrode core 30 except for the part to which the positive electrode lead 20 is connected. The positive electrode 11 can be produced, for example, by applying a positive electrode composite slurry containing a positive electrode active material, a binder, a conductive material, and the like to the surface of the positive electrode core 30, drying the coating, and then compressing it to form the positive electrode composite layer 31 on both sides of the positive electrode core 30.
[0022] Examples of the conductive material contained in the positive electrode mixture layer 31 include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. Examples of the binder contained in the positive electrode mixture layer 31 include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, and polyolefin. These resins may be used in combination with cellulose derivatives such as carboxymethylcellulose (CMC) or a salt thereof, polyethylene oxide (PEO), and the like.
[0023] The positive electrode 11 contains, as positive electrode active materials, a lithium transition metal composite oxide (A) having a volume-based median diameter (D50) of 0.6 μm to 3 μm and a lithium transition metal composite oxide (B) having a D50 of 6 μm to 25 μm (hereinafter simply referred to as "composite oxides (A) and (B)"). In this embodiment, only the composite oxides (A) and (B) are contained as the positive electrode active materials. However, the positive electrode mixture layer 31 may contain composite oxides other than the composite oxides (A) and (B) or other compounds within a range that does not impair the object of the present disclosure.
[0024] The volume-based median diameter (D50) refers to the particle size at which the cumulative frequency is 50% from the smallest particle size in the volume-based particle size distribution, and is also called the median diameter. The particle size and particle size distribution of the complex oxide can be measured using a laser diffraction type particle size distribution measuring device (e.g., MT3000II manufactured by Microtrack Bell Co., Ltd.) with water as the dispersion medium.
[0025] The composite oxide (A) is a secondary particle formed by agglomeration of large primary particles having an average particle size of 0.5 μm or more, or a composite oxide particle substantially composed of a single particle. The composite oxide (A) substantially composed of a single particle means a particle in which the grain boundary of the primary particles cannot be confirmed when observed at an appropriate magnification using a scanning electron microscope (SEM). When the composite oxide (A) is a secondary particle, the average particle size of the primary particles is 0.5 μm to 3 μm. On the other hand, the composite oxide (B) is a secondary particle formed by agglomeration of small primary particles having an average particle size of, for example, 0.3 μm or less.
[0026] When the composite oxide (A) is a secondary particle, the grain boundaries of the primary particles are observed in the particle cross section observed by SEM. For example, the composite oxide (A) is composed of 100 or less, several to several tens, for example, 2 to 5 primary particles, and the composite oxide (B) is composed of 10,000 to 5,000,000 primary particles. The particle size of the primary particles is measured as the Feret diameter of the region (primary particle) surrounded by the grain boundaries in the SEM image of the particle cross section of the composite oxide. The average particle size of the primary particles is calculated by averaging the particle sizes of 100 primary particles.
[0027] The composite oxide (A) contains 65 mol % or more of Ni based on the total number of moles of metal elements excluding Li. The composite oxide (B) contains 70 mol % or more of Ni based on the total number of moles of metal elements excluding Li. By using a positive electrode active material with a high Ni content, a battery with a high energy density can be obtained. The Ni content of the composite oxide (A) may be lower than the Ni content of the composite oxide (B). In addition, boron is present at least on the particle surface of the composite oxide (B).
[0028] The composite oxides (A) and (B) may contain metal elements other than Li, Ni, and B. Examples of the metal elements include Co, Mn, Al, Ti, Zr, Mg, Fe, Cu, Zn, Sn, Na, K, Ba, Sr, Ca, W, Mo, Nb, and Si. The compositions of the composite oxides (A) and (B) may be different from each other. The composite oxide (A) may or may not contain boron. On the other hand, the composite oxide (B) contains boron, and boron is present at least on the particle surface of the composite oxide (B).
[0029] An example of a suitable composite oxide (A) is represented by the general formula Li a Ni b Co c Mn d B e O f(wherein, 0.8≦a≦1.2, b≧0.70, c≦0.10, 0.03≦d≦0.12, 0≦e≦0.05, 1≦f≦2, b+c+d+e=1). The molar fraction of metal elements in the entire complex oxide particle is measured by inductively coupled plasma (ICP) atomic emission spectrometry.
[0030] The particle surface of the composite oxide (A) is smoother than that of the composite oxide (B). The sphericity of the composite oxide (A) is not particularly limited, but is preferably 0.7 or more and 0.9 or less. The sphericity can be calculated by the following formula based on a particle image taken by irradiating a sample flow containing composite oxide particles with a strobe light.
[0031] Sphericity = (perimeter of a circle with the same area as the particle image) / (perimeter of the particle image) The compressive strength of the composite oxide (A) may be, for example, 250 MPa or more, or 350 MPa or more. In this case, compared with the case where the above range is not satisfied, cracking of particles due to charging and discharging is suppressed, which contributes to improvement of high-temperature cycle characteristics. The upper limit of the compressive strength of the composite oxide (A) is not particularly limited, but is, for example, 1500 MPa or less. The compressive strength of the composite oxide (A) is measured by the method specified in JIS-R1639-5.
[0032] The composite oxide (A) can be prepared, for example, by the following procedure.
[0033] First, a lithium compound such as lithium hydroxide and an oxide containing nickel and the above-mentioned metal element are mixed in a mixing ratio based on the target composite oxide (A). At this time, a potassium compound is further added to the mixture. Next, the mixture containing the lithium compound, the oxide containing nickel and the metal element, and the potassium compound or the sodium compound is fired in air or in an oxygen stream. Thereafter, the fired product obtained is washed with water to remove the potassium compound or the sodium compound adhering to the surface of the fired product.
[0034] The composite oxide (A) is synthesized by the above method. Although the detailed theory behind the increase in the size of the primary particles is not clear, it is believed that the addition of a potassium compound to the above mixture causes the growth of single crystal particles during firing to proceed uniformly throughout the entire mixture phase.
[0035] The firing temperature in the above step is, for example, 600°C to 1050°C, and the higher the temperature, the larger the primary particles tend to be. When the firing temperature is 600 to 1050°C, the firing time is about 1 to 100 hours. On the premise that the flux compound is removed by washing with water or the like, the composite oxide (A) can also be obtained by growing crystals together with oxides having low melting points such as Na and K. Examples of the potassium compound include potassium hydroxide (KOH) and its salts, potassium acetate, and the like. The potassium compound is added in an amount of, for example, 0.1 to 100 mass% or less with respect to the composite oxide (A) to be synthesized.
[0036] As described above, the composite oxide (B) contains boron. Boron may be present on the surface of the secondary particles of the composite oxide (B) as well as on the surface of the primary particles. A part of the boron may also be present inside the primary particles and form a solid solution with other metal elements contained in the composite oxide (B). However, from the viewpoint of suppressing side reactions between the active material and the electrolyte, it is preferable that boron is present in large amounts on the surface of the secondary particles.
[0037] An example of a suitable composite oxide (B) is represented by the general formula Li a Ni b Co c Mn d B e O f (wherein, 0.8≦a≦1.2, b≧0.70, c≦0.10, 0.03≦d≦0.12, 0≦e≦0.05, 1≦f≦2, b+c+d+e=1). In the composite oxide (B), the content (number of moles) of boron relative to the total number of moles of metal elements excluding Li is preferably 0.1 to 5 mol%, more preferably 0.2 to 2 mol%. If the amount of boron is within this range, particle cracking can be efficiently suppressed.
[0038] The composite oxide (B) is characterized in that, when the first particles are particles having a particle size larger than the 70% particle size (D70) based on volume and the second particles are particles having a particle size smaller than the 30% particle size (D30) based on volume, the molar fraction (B1) of boron in the first particles relative to the total moles of metal elements excluding Li is larger than the molar fraction (B2) of boron in the second particles relative to the total moles of metal elements excluding Li. The amount of boron contained in the first and second particles is measured by ICP, like other metal elements.
[0039] That is, the composite oxide (B) is a particle in which the ratio (B1 / B2) of the molar fraction (B1) of boron contained in the first particle to the molar fraction (B2) of boron contained in the second particle is at least 1. By using such a composite oxide (B), side reactions with the electrolyte can be efficiently suppressed, and a battery having high energy density and excellent high-temperature cycle characteristics can be obtained due to a synergistic effect with the composite oxide (A).
[0040] Here, D70 means a particle size where the cumulative frequency is 70% from the smallest particle size in the volumetric particle size distribution. Similarly, D30 means a particle size where the cumulative frequency is 30% from the smallest particle size in the volumetric particle size distribution. For example, D70 is 9 μm to 19 μm, and D30 is 3 μm to 13 μm.
[0041] The ratio (B1 / B2) of the molar fraction (B1) of boron contained in the first particle to the molar fraction (B2) of boron contained in the second particle is preferably 1.1 or more, more preferably 1.5 or more, and may be 3.0 or more. The upper limit of (B1 / B2) is not particularly limited, but is, for example, 10. An example of a suitable range of (B1 / B2) is 1.5 to 3.5, or 2.5 to 3.5.
[0042] As long as the molar fractions (B1) and (B2) of boron measured by ICP satisfy the condition (B1)>(B2), the first particles may contain particles having a molar fraction (B1) of boron equal to or lower than the molar fraction (B2) of boron of the second particles. The second particles may contain particles having a molar fraction (B2) of boron higher than the molar fraction (B1) of boron on the particle surface of the first particles. Preferably, (B2)>0, and boron is present on the surfaces of both the first particles and the second particles.
[0043] In the composite oxide (B), boron is generally present in the form of a boron compound. The boron compound may contain Li. As described later, boric acid (H 3 BO 3 ), boron oxide (B 2 O 3 ), lithium borate (LiBO 2 , Li 2 B 4 O 7 When boron compounds such as boron oxide and boron fluoride are used as boron sources, they may react with the Li present on the particle surface during firing to produce boron compounds containing Li and B.
[0044] The boron compound may be formed in a layer so as to cover the particle surface (secondary particle surface) of the composite oxide (B), or may be scattered on the particle surface, but it is preferable that the boron compound does not completely cover the entire particle surface. That is, there are areas on the particle surface of the composite oxide (B) where the boron compound is not attached. When the boron compound is present in particulate form, the particle size of the boron compound is generally smaller than the particle size of the primary particles constituting the composite oxide (B). The particles of the boron compound can be confirmed by SEM. It is preferable that the boron compound is attached over a wide area of the particle surface of the composite oxide (B) without being unevenly distributed in a part of the particle surface.
[0045] The thickness of the boron compound on the particle surface of the composite oxide (B) is preferably 100 nm or less, more preferably 50 nm or less. The thickness of the boron compound is more preferably 10 nm or more. A suitable example of the thickness of the boron compound is 10 nm to 50 nm. If the thickness of the boron compound is within this range, the high-temperature cycle characteristics can be efficiently improved without impairing the rate characteristics and the like.
[0046] Moreover, the coverage of boron on the surfaces of the first and second particles (hereinafter sometimes referred to as "surface coverage") is preferably 99% or less, more preferably 90% or less, and particularly preferably 70% or less. In this case, the high-temperature cycle characteristics can be efficiently improved without impairing the rate characteristics, etc. of the battery. If the surface coverage is 100%, it means that the entire particle surface is covered with the boron compound. In other words, if the surface coverage is less than 100%, there is an area on the particle surface where the boron compound is not attached. The lower limit of the surface coverage of boron is, for example, 50%.
[0047] The surface coverage of boron is measured by electron probe microanalyzer (EPMA) or X-ray photoelectron spectroscopy (XPS). In EPMA, the surface coverage of boron is determined by the ratio of the peak area of boron to the total peak area of metal elements excluding Li. In XPS, it is calculated from the molar fraction of boron to the total moles of metal elements excluding Li (if the molar fraction of boron is 1, the surface coverage is 100%). In addition, in XPS, the elements on the particle surface are identified. In the XPS measurement, the X-ray irradiation spot diameter is set to 1 mmΦ or more, and the first particle and the second particle are each selected and placed in the irradiation spot. In this case, several hundred particles are contained in the irradiation spot, so the molar fraction of boron is measured as the average value of multiple particles.
[0048] The composite oxide (B) can be prepared, for example, by the following procedure.
[0049] First, a lithium source such as lithium hydroxide is added to two kinds of nickel compounds (X1) and (X2) that contain at least Ni, do not contain Li and B, and have different D50s, and the compounds are fired to synthesize lithium nickel composite oxides (Y1) and (Y2) that have different D50s (step 1). An example of the composite compound is a composite oxide or hydroxide that contains Ni, Co, and Mn. At this time, one kind of lithium nickel composite oxide may be classified to obtain two kinds of lithium nickel composite oxides that have different D50s. A conventionally known method may be applied to the classification. The obtained lithium nickel composite oxides (Y1) and (Y2) may be washed with water. By washing with water, not only the amount of Li present on the particle surface of the composite oxide but also the amount of Li present inside the particles is reduced, and voids are generated inside the washed composite oxide particles.
[0050] Next, a boron source is added to each of the lithium nickel composite oxides (Y1) and (Y2), and boron is composited onto the particle surface, followed by calcination to synthesize the lithium transition metal composite oxides (Z1) and (Z2) (step 2). The composite oxides (Z1) and (Z2) are then mixed to obtain the composite oxide (B). An example of the boron source is boric acid (H 3 BO 3 For the composite, a dry particle composite device (for example, NOB-130 manufactured by Hosokawa Micron Corporation) or the like is used. At this time, a lithium source such as lithium hydroxide may be added together with the boron source.
[0051] In the above step 2, H for the lithium nickel composite oxide (Y1) 3 BO 3 The amount of H added to the lithium nickel composite oxide (Y2) was 3 BO 3 By making the amount of boron added larger than the amount of boron added, a state in which the molar fraction (B1) of boron on the surfaces of the first and second particles of the composite oxide (B) is greater than the molar fraction (B2) of boron can be obtained. The firing temperature in the above step 2 is, for example, 200°C to 500°C.
[0052] By adjusting whether or not the composite oxides (Y1) and (Y2) are washed with water and the calcination temperature, the amount and thickness of the boron compound coated on the surface of the first particle and the second particle of the composite oxide (B) can be adjusted. By calcining the washed composite oxides (Y1) and (Y2) with a boron source at high temperature, a composite oxide having a small amount of surface coverage by the boron compound can be synthesized. Even if the composite oxides (Y1) and (Y2) are washed with water, if they are calcined at a low temperature, boron does not enter the voids inside the particles, and the amount and thickness of the surface coverage of the boron compound are approximately the same as when they are not washed with water. Here, the high temperature is, for example, 350°C to 500°C, and the low temperature is, for example, 200°C to 325°C.
[0053] As described above, the positive electrode active material is a mixture of the composite oxide (A) and the composite oxide (B). The content of the composite oxide (A) relative to the mass of the positive electrode active material is, for example, 5 to 65 mass%, preferably 10 to 60 mass%, and particularly preferably 20 to 55 mass%. The content of the composite oxide (B) relative to the mass of the positive electrode active material is, for example, 35 to 95 mass%, preferably 40 to 90 mass%, and particularly preferably 45 to 80 mass%.
[0054] The density of positive electrode mixture layer 31 is preferably 3.55 g / cc or more, and more preferably 3.60 g / cc or more. If the mixture ratio of complex oxides (A) and (B) is within the above range, the packing property of the particles is improved, and the packing density of positive electrode mixture layer 31 can be increased, resulting in a battery with high energy density and excellent high-temperature cycle characteristics.
[0055] [Negative electrode] The negative electrode 12 has a negative electrode core and a negative electrode composite layer provided on the surface of the negative electrode core. For the negative electrode core, a foil of a metal such as copper that is stable in the potential range of the negative electrode 12, a film with the metal disposed on the surface layer, or the like can be used. The negative electrode composite layer contains a negative electrode active material and a binder, and is preferably provided on both sides of the negative electrode core except for the part to which the negative electrode lead 21 is connected. The negative electrode 12 can be produced, for example, by applying a negative electrode composite slurry containing a negative electrode active material and a binder to the surface of the negative electrode core, drying the coating, and then compressing it to form a negative electrode composite layer on both sides of the negative electrode core.
[0056] The negative electrode mixture layer contains, as the negative electrode active material, for example, a carbon-based active material that reversibly absorbs and releases lithium ions. Suitable carbon-based active materials are graphites such as natural graphite, such as flake graphite, lump graphite, and earthy graphite, and artificial graphite, such as lump artificial graphite (MAG) and graphitized mesophase carbon microbeads (MCMB). In addition, the negative electrode active material may be a Si-based active material composed of at least one of Si and a Si-containing compound, or a carbon-based active material and a Si-based active material may be used in combination.
[0057] The binder contained in the negative electrode mixture layer may be, as in the case of the positive electrode 11, a fluororesin, PAN, polyimide, acrylic resin, polyolefin, or the like, but it is preferable to use styrene-butadiene rubber (SBR). The negative electrode mixture layer preferably further contains CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof, polyvinyl alcohol (PVA), or the like. Among them, it is preferable to use SBR in combination with CMC or a salt thereof, or PAA or a salt thereof.
[0058] [Separator] A porous sheet having ion permeability and insulating properties is used for the separator 13. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The material of the separator 13 is preferably a polyolefin such as polyethylene or polypropylene, or cellulose. The separator 13 may have either a single-layer structure or a laminated structure. A heat-resistant layer or the like may be formed on the surface of the separator. EXAMPLES
[0059] The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.
[0060] <Example 1> [Preparation of composite oxide A] Obtained by coprecipitation, D50 is 15μm, composition is Ni 0.80 Co 0.10 Mn 0.10 (OH) 2 The nickel-cobalt-manganese composite hydroxide was calcined at 500°C to obtain a nickel-cobalt-manganese composite oxide. Next, lithium hydroxide and the nickel-cobalt-manganese composite oxide thus prepared were mixed so that the molar ratio of Li to the total amount of Ni, Co, and Mn was 1.05:1, and a potassium compound was added to the mixture in an amount of 20 mass% relative to the composite oxide. This mixture was calcined in an oxygen atmosphere at 750°C for 72 hours, and then crushed and washed with water to remove the potassium compound, thereby obtaining composite oxide A.
[0061] The composition of composite oxide A was analyzed by ICP, and the results showed that Li 1.01 Ni 0.80 Co 0. 10 Mn 0.10 O 2 The D50 value of composite oxide A was 2.3 μm. The cross section of composite oxide A after CP processing was observed by SEM, and the average particle size of the primary particles of composite oxide A was 1.4 μm. Approximately 95% or more of the total particles of composite oxide A had a single particle structure, and some particles had a pseudo-aggregated structure in which 3 to 10 or so primary particles were bonded together.
[0062] [Preparation of composite oxide B] Obtained by coprecipitation, with the composition Ni 0.85 Co 0.08 Mn 0.07 (OH) 2The nickel-cobalt-manganese composite hydroxide was calcined at 500°C and then sieved using a vibrating sieve (sieve opening 300 μm, shaking time 30 minutes) to obtain nickel-cobalt-manganese composite oxide (X1) with a large particle size and D50 of 14 μm that remained on the sieve, and nickel-cobalt-manganese composite oxide (X2) with a small particle size and D50 of 7 μm that passed through the sieve.
[0063] Next, lithium hydroxide and the large particle size nickel-cobalt-manganese composite oxide (X1) were mixed so that the molar ratio of Li to the total amount of Ni, Co, and Mn was 1.08: 1. This mixture was fired at 700°C in an oxygen atmosphere for 8 hours and then pulverized to obtain a large particle size lithium composite oxide (Y1).
[0064] Lithium hydroxide and a small particle size nickel-cobalt-manganese composite oxide (X2) were mixed so that the molar ratio of Li to the total amount of Ni, Co, and Mn was 1.08: 1. This mixture was fired at 700°C in an oxygen atmosphere for 8 hours and then pulverized to obtain a small particle size lithium composite oxide (Y2).
[0065] Next, a large-particle lithium composite oxide (Y1) and boric acid (H 3 BO 3 ) is the total amount of Ni, Co, Mn, and H 3 BO 3 The mixture was dry mixed so that the molar ratio of B in the mixture was 100:1.5, and boron was composited on the particle surface. The mixture was fired at 300°C for 8 hours in an oxygen atmosphere and then pulverized to obtain a large-particle lithium composite oxide (Z1) in which boron was present at least on the particle surface.
[0066] In addition, small particle size tium composite oxide (Y2) and H 3 BO 3 The total amount of Ni, Co, and Mn, and H 3 BO 3The mixture was dry mixed so that the molar ratio of B in the mixture was 100:0.5, and boron was composited on the particle surface. This mixture was fired at 300°C for 8 hours in an oxygen atmosphere and then pulverized to obtain a small-particle lithium composite oxide (Z2) in which boron was present at least on the particle surface.
[0067] The lithium composite oxides (Z1) and (Z2) were mixed in a mass ratio of 1:1 to form composite oxide (B), and composite oxide A was mixed in an amount of 50 mass % based on the total mass of the positive electrode active material to form a positive electrode active material.
[0068] In the composite oxide (B), the molar fraction (B1) of boron in the first particles having a particle size larger than D70 on a volume basis was 0.015, and the molar fraction (B2) of boron on the surface of the second particles having a particle size smaller than D30 on a volume basis was 0.005, and the ratio (B1 / B2) was 3.0. In addition, the coverage of boron on the surfaces of the first and second particles was 96%. As described above, the amount (mole fraction) of boron contained in the first and second particles is measured by ICP. In addition, the amount (surface coverage) of boron present on the particle surface is measured by EPMA.
[0069] The composition of composite oxide B was analyzed by ICP, and the results showed that Li 1.01 Ni 0.85 Co 0.08 Mn 0.07 B 0.01 O 2 The particle size distribution of composite oxide B was D50 11 μm, D70 14 μm, and D30 7.5 μm. The cross section of composite oxide B after the CP processing was observed by SEM, and the average particle size of the primary particles of composite oxide B was 0.15 μm.
[0070] [Preparation of positive electrode] The positive electrode active material, acetylene black, and polyvinylidene fluoride (PVdF) were mixed in a solid content mass ratio of 96.3:2.5:1.2, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added, followed by kneading to prepare a positive electrode composite slurry. The positive electrode composite slurry was applied to both sides of a positive electrode core made of aluminum foil, and the coating was dried. The coating was then rolled using a roller and cut to a predetermined electrode size to obtain a positive electrode in which a positive electrode composite layer was formed on both sides of the positive electrode core. An exposed portion was provided in part of the positive electrode, exposing the surface of the positive electrode core.
[0071] [Preparation of negative electrode] Natural graphite was used as the negative electrode active material. The negative electrode active material, sodium carboxymethylcellulose (CMC-Na), and styrene-butadiene rubber (SBR) were mixed in an aqueous solution at a solid content mass ratio of 100:1:1 to prepare a negative electrode composite slurry. The negative electrode composite slurry was applied to both sides of a negative electrode core made of copper foil, and the coating film was dried. The coating film was then rolled using a roller and cut to a predetermined electrode size to obtain a negative electrode in which a negative electrode composite layer was formed on both sides of the negative electrode core. An exposed portion was provided in part of the negative electrode, where the surface of the negative electrode core was exposed.
[0072] [Preparation of non-aqueous electrolyte] Lithium hexafluorophosphate (LiPF 6 ) was dissolved in the mixed solvent at a concentration of 1.0 mol / L. Furthermore, vinylene carbonate (VC) was dissolved in the mixed solvent at a concentration of 2.0 mass % to prepare a non-aqueous electrolyte solution.
[0073] [Battery construction] An aluminum lead was attached to the exposed part of the positive electrode, and a nickel lead was attached to the exposed part of the negative electrode, and the positive and negative electrodes were spirally wound with a polyolefin separator interposed therebetween, and then pressed in the radial direction to produce a flat wound electrode body. This electrode body was housed in an exterior body made of an aluminum laminate sheet, and the nonaqueous electrolyte was injected, and the opening of the exterior body was sealed to obtain a nonaqueous electrolyte secondary battery with a design capacity of 650 mAh.
[0074] <Example 2> A positive electrode active material and a nonaqueous electrolyte secondary battery were produced in the same manner as in Example 1, except that in the preparation of composite oxide B, the firing temperature in the synthesis of the lithium composite oxides (Z1) and (Z2) was changed to 400°C.
[0075] <Comparative Example 1> A positive electrode active material and a non-aqueous electrolyte secondary battery were produced in the same manner as in Example 1, except that composite oxide A was not used (composite oxide B was 100%).
[0076] <Comparative Example 2> A positive electrode active material and a non-aqueous electrolyte secondary battery were produced in the same manner as in Example 2, except that composite oxide A was not used (composite oxide B was 100%).
[0077] <Comparative Example 3> No composite oxide A was used (composite oxide B was 100%), and no sieving was performed during the synthesis of composite oxide B. The obtained lithium composite oxide and boric acid (H 3 BO 3 ) is the total amount of Ni, Co, Mn, and H 3 BO 3 A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 1, except that the materials were dry-mixed so that the molar ratio of B in the material was 100:1.
[0078] <Comparative Example 4> No composite oxide A was used (composite oxide B was 100%), and no sieving was performed during the synthesis of composite oxide B. The obtained lithium composite oxide and boric acid (H 3 BO3 ) is the total amount of Ni, Co, Mn, and H 3 BO 3 A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 2, except that the materials were dry-mixed so that the molar ratio of B in the material was 100:1.
[0079] [High temperature cycle test] Each battery of the Examples and Comparative Examples was charged at a constant current of 0.5 It in a temperature environment of 60° C. until the battery voltage reached 4.2 V, and then charged at a constant voltage until the current value reached 1 / 50 It at 4.2 V. Thereafter, the battery was discharged at a constant current of 0.5 It until the battery voltage reached 2.5 V. This charge / discharge cycle was repeated 150 times.
[0080] [Evaluation of capacity retention rate after cycle testing] For each battery of the Examples and Comparative Examples, the discharge capacity at the first cycle and the discharge capacity at the 150th cycle of the cycle test were determined, and the capacity retention rate was calculated by the following formula.
[0081] Capacity retention rate (%) = (150th cycle discharge capacity ÷ 1st cycle discharge capacity) × 100 [Evaluation of filling property of positive electrode mixture layer] For each positive electrode prepared in the examples and comparative examples, a rectangular electrode plate (thickness 200 μm) with a total length of 1 m and a composite layer formed on both sides was prepared for packing evaluation. This electrode plate was compressed by changing the compression conditions (gap value) using a rolling machine (manufactured by NAKNOR) with a roll diameter of 750 mm, and punched out to Φ40 mm after compression. For each electrode plate, the packing density under the compression conditions where the electrode plate elongation amount was 1% is shown in Table 1. In Table 1, the positive electrode composite layer with a high packing density is indicated as ◯ (particularly high is indicated as ◎), and the positive electrode composite layer with a low packing density is indicated as × (particularly low is indicated as XX).
[0082] [Table 1]
[0083] As shown in Table 1, all of the batteries of the examples have higher capacity retention rates after cycle testing and are superior in high-temperature cycle characteristics compared to the batteries of the comparative examples. [Explanation of symbols]
[0084] 10 Nonaqueous electrolyte secondary battery 11 Positive electrode 12 Negative electrode 13 Separator 14 Electrode body 16 Outer can 17 Sealing body 18,19 Insulating plate 20 Positive lead 21 Negative lead 22 Grooved part 23 Internal terminal board 24 Lower valve body 25 Insulating materials 26 Upper valve 27 Cap 28 Gasket 30 Positive electrode core 31 Positive electrode mixture layer
Claims
1. The battery includes a positive electrode including a positive electrode active material, a negative electrode, and a non-aqueous electrolyte, The positive electrode includes, as the positive electrode active material, a lithium transition metal composite oxide (A) which is a secondary particle formed by agglomeration of primary particles having an average particle size of 0.5 μm or more, or which is substantially composed of a single particle, and has a volume-based median size (D50) of 0.6 μm to 3 μm, and a lithium transition metal composite oxide (B) which is a secondary particle formed by agglomeration of primary particles having an average particle size of 0.3 μm or less, and has a volume-based median size (D50) of 6 μm to 25 μm; The lithium transition metal composite oxide (A) has the general formula Li a Ni b Co c Mn d B e O f (wherein 0.8≦a≦1.2, b≧0.70, c≦0.10, 0.03≦d≦0.12, 0≦e≦0.05, 1≦f≦2, and b+c+d+e=1), The lithium transition metal composite oxide (B) has the general formula Li a Ni b Co c Mn d B e O f (wherein 0.8≦a≦1.2, b≧0.70, c≦0.10, 0.03≦d≦0.12, 0.001≦e≦0.05, 1≦f≦2, and b+c+d+e=1), in which boron is present at least on the particle surface of the oxide, Regarding the lithium transition metal composite oxide (B), when particles having a particle size larger than the 70% particle size (D70) based on volume are defined as first particles, and particles having a particle size smaller than the 30% particle size (D30) based on volume are defined as second particles, a molar fraction (B1) of boron with respect to the total number of moles of metal elements excluding Li in the first particles is greater than a molar fraction (B2) of boron with respect to the total number of moles of metal elements excluding Li in the second particles.
2. 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein the content of the lithium transition metal composite oxide (A) relative to the mass of the positive electrode active material is 20 to 55 mass %.
3. 3 . The nonaqueous electrolyte secondary battery according to claim 1 , wherein a coverage of the surfaces of the first particles and the second particles with boron is 70% or less.
Citation Information
Patent Citations
Cathode active material for lithium ion secondary battery or cathode active material for sodium ion secondary battery, and manufacturing method thereof
JP2019033016A
Positive active material for nonaqueous-electrolyte secondary battery
WO2017056364A1
Non-aqueous electrolyte secondary battery
WO2017094237A1
Positive electrode active material for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery
WO2017098679A1
Positive electrode active material for nonaqueous electrolyte secondary batteries, method for producing same, positive electrode mixture paste for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery
WO2017199891A1